2023
DOI: 10.3389/fmicb.2023.1089143
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culture and characterization of Arsenophonus symbionts from two insect species reveal loss of infectious transmission and extended host range

Abstract: Vertically transmitted “Heritable” microbial symbionts represent an important component of the biology and ecology of invertebrates. These symbioses evolved originally from ones where infection/acquisition processes occurred within the environment (horizontal transmission). However, the pattern of evolution that follows transition from horizontal to vertical transmission is commonly obscured by the distant relationship between microbes with differing transmission modes. In contrast, the genus Arsenophonus prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…To gain a precise view of the tempo and mode of evolution during the transition to persistent endosymbiosis, we leveraged the wide diversity of host-associated lifestyles in the gammaproteobacterial genus Arsenophonus. Within this clade, there are environmentally acquired extracellular pathogens, extracellular endosymbionts with mixed modes of transmission, intracellular facultative endosymbionts with vertical transmission, and obligate vertically transmitted endosymbionts where the partners are co-dependent [6][7][8][9][10]. Importantly, extracellular pathogens and endosymbionts with mixed modes of transmission are very closely related.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain a precise view of the tempo and mode of evolution during the transition to persistent endosymbiosis, we leveraged the wide diversity of host-associated lifestyles in the gammaproteobacterial genus Arsenophonus. Within this clade, there are environmentally acquired extracellular pathogens, extracellular endosymbionts with mixed modes of transmission, intracellular facultative endosymbionts with vertical transmission, and obligate vertically transmitted endosymbionts where the partners are co-dependent [6][7][8][9][10]. Importantly, extracellular pathogens and endosymbionts with mixed modes of transmission are very closely related.…”
Section: Resultsmentioning
confidence: 99%
“…Seven Arsenophonus isolates were isolated to pure culture and sequenced within this project: A. nasoniae isolates aNv_UK, aNv_CH and aNv_CAN derived from Nasonia vitripennis from the UK, Switzerland and Canada respectively, A. nasoniae aPv from Pachycrepoideus vindemmiae and the Arsenophonus strain aPb from the butterfly Polyommatus bellargus [9], Arsenophonus nasoniae strain aIh previously identified in the parasitoid wasp Ixodiphagus hookeri from a questing Ixodes ricinus tick in The Netherlands [28] and Arsenophonus apicola strain aApi_AU from Australian honey bees described in [29]. A further strain, Ca.…”
Section: Methods Details Isolate Collection Culture Sequencing and As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Arsenophonus and Sodalis are among the symbionts most frequently observed in arthropod hosts including psyllid lineages ( Thao et al , 2000a ; Spaulding and von Dohlen, 2001 ; Hansen et al , 2007 ; Moran et al , 2008 ; Sloan and Moran, 2012 ; Arp et al , 2014 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), Symbiopectobacterium is the lineage identified for the first time in Psylloidea. Arsenophonus have been found in diverse insect groups, including wasps ( Gherna et al , 1991 ; Nadal-Jimenez et al , 2023 ), bees (Hymenoptera: Apoidea) ( Nadal-Jimenez et al , 2022a ), aphids ( Russell et al , 2003 ; Wulff and White, 2015 ; Tian et al , 2019 ; Zhang et al , 2021 ; Yorimoto et al , 2022 ), psyllids ( Spaulding and von Dohlen, 1998 , 2001 ; Subandiyah et al , 2000 ; Thao et al , 2000a ; Hansen et al , 2007 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), whiteflies ( Thao and Baumann, 2004 ; Chiel et al , 2007 ; El Hamss et al , 2021 ), triatomine bugs (Hemiptera: Heteroptera) ( Hypsa and Dale, 1997 ), lice (Psocodea: Anoplura) ( Sasaki-Fukatsu et al , 2006 ; Allen et al , 2007 ; Kirkness et al , 2010 ), louse flies ( Dale et al , 2006 ; Nováková et al , 2009 , 2016 ), and ticks (Arachnida: Ixodida) ( Grindle et al , 2003 ). The types of symbiotic relationships with hosts exhibit a wide diversity from parasitism ( e.g.…”
Section: Discussionmentioning
confidence: 99%